Young Substance Abusers and Precarious Employment: Trajectories and Anchoring Dynamics - Morissette, Pauline; Maranda, Marie-France; Lessard, Danielle (Canadian Journal of Counselling and Psychotherapy, 2007)
A study was undertaken to understand the chain of family, school, and employment factors that led a sample of young (18–30) psychoactive substance abusers into precarious employment situations, based on their personal narratives. Substance abuse was measured according to DAST-20 and SMAST scales. Three types of precarious employment trajectories emerged: concentrated precarization in a dynamic of inferiorization, integrated precarization (in either an identifi cation or a parentifi cation dynamic), and unexpected precarization in a dynamic of intensifi cation. A discussion of the results points to the importance of developing an integrated multilevel intervention approach in vocational counselling for this clientele.